Autonomy support in toddlerhood: Similarities and contrasts between mothers and fathers. - Hughes, Claire; Lindberg, Anja; Devine, Rory T (American Psychological Association (APA), 2018)
Infant exploration often hinges on parental autonomy support (i.e., parental behaviors that support children's goals, interests, and choices), a construct that is widely applied in family studies of school-age children and adolescents but less studied in infants and toddlers. Notable gaps concern the equivalence, similarities, and contrasts between mothers' and fathers' autonomy support and the correlates of individual differences in autonomy support. To address these underresearched topics, we conducted parallel home-based structured play observations of 195 infants (Mage = 14.42 months, SD = .59) in dyadic interaction with mothers and fathers. Confirmatory factor analyses demonstrated measurement invariance across parent gender, enabling comparisons that revealed significantly moderately higher levels of autonomy support in mothers than in fathers. Individual differences in autonomy support were unrelated to either parental personality or child temperament, highlighting the potential importance of dyadic characteristics. Consistent with this view, whereas maternal autonomy support did not differ by child gender, fathers with sons displayed less autonomy support than did fathers with daughters. (PsycINFO Database Record (c) 2018 APA, all rights reserved).
Keywords: Adult; Factor Analysis, Statistical; Fathers; Female; Humans; Individuality; Infant; Interpersonal Relations; Male; Middle Aged; Mothers; Parenting; Personal Autonomy; Personality; Play and Playthings; Sex Factors; Temperament; Young Adult